Granger Causality Between The Stock Market Index and Macroeconomic Variables. A Study of Malaysia and Singapore - Sircar, Shadee Mosaddek (2009)
This paper investigates the causal relationships that may be present between the stock market index of developing countries and their macroeconomic variables based on the Vector Error Correction Model (VECM) framework. The countries Malaysia and Singapore are chosen for the purpose of this paper, where FTSE KLCI index and the FTSE STI index are used to represent the stock market performances respectively for each country. The four macroeconomic variables analyzed and used in this paper are Consumer Price Index (CPI), Industrial Production Index (IPI), 3 month T-bill rate (IR) and exchange rate against the US Dollar (ER). The timeframe analyzed was between May 1999 and May 2009, were monthly data was collected and used for the analyses A brief history and explanation of both the stock markets and the various macroeconomic variables used were given. Following this the theoretical background based on previous literature and economic theory was investigated. This showed that although Singapore and Malaysia may not be considered economies with strong form efficiencies, but information relayed from the macroeconomic variables do in fact have a relation and causation with the stock market. Using the simple dividend discount model, the reasons behind the relationship between the stock market and the various macroeconomic variables were shown. The papers own empirical research based on the VECM framework showed that both Singapore and Malaysia had variables that had univariate relationships with the stock market. For Malaysia it was found that the FTSE KLCI was actually influenced by the countries consumer price index in the short run, which was in line with previous literature’s argument. It was also found that FTSE KLCI influenced the industrial production index and not the other way around. For Singapore however the STI was found influenced by the interest rate and its fluctuations showing a strong monetarist hold on the economy. Analysis showed that the STI also influenced both the countries exchange rate and the consumer price index. It was therefore found that the Singaporean stock market was more directly interrelated with its macroeconomic indicators compared to Malaysia The paper however was unable to find all the relationships proclaimed by literature to be present in this model for both countries. This is normal as this can be attributed to the difference of data sample processed and due to other differences in analytical technique.